2-Mercaptobenzimidazole, 2-Mercaptobenzothiazole, and Thioglycolic Acid as Additives for Electrolytic Ni Plating - Gezerman, Ahmet Ozan; Corbacioglu, Burcu Didem (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
In this study, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, and thioglycolic acid were used as additives in the nickel electroplating bath to improve the physical properties of the plated materials, such as corrosion resistance, electrical resistivity, plating thickness, and adhesion force. Physical tests on the resulting plated materials were conducted using a visible-region spectrophotometer and electron microscope; in addition, the hardness of the nickel plating was investigated using a Falex tester. The problem of wastewater production associated with nickel plating can be eliminated using 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, and thioglycolic acid.
Keywords: Electrolytic Ni plating; 2-Mercaptobenzimidazole; 2-Mercaptobenzothiazole; Thioglycolic acid; NICKEL; ACETYLACETONATE; FABRICATION; COMPLEXES; COATINGS; GOLD; Science & Technology - Other Topics